Postoperative Quality of Life in Patients with Pyogenic Spondylodiscitis - Abboud, Tammam; Krolikowska-Fluori, Magdalena; Melich, Patrick; Rohde, Veit; Schatlo, Bawarjan (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2022)
Background Pyogenic spondylodiskitis affects a fragile patient population frequently fraught with severe comorbidities. Data on long-term outcomes, especially for patients undergoing surgery, are scarce. The aim of this study was to assess the long-term quality of life after surgical instrumentation.Methods Data of 218 patients who were treated for spondylodiskitis at our institution between January 2008 and July 2017 were reviewed. In-hospital death and mortality rates at 1 year and follow-up were assessed. A survey was conducted using the following questionnaires: Oswestry Disability Index (ODI), Short Form Work Ability Index (SF-WAI), 36-Item Short Form Health Survey (SF-36), and Short Form McGill Pain Questionnaire (SF-MPQ). We investigated the correlation between the assessed variables and clinical data including patient age, comorbidity score at admission, number of operated levels, corpectomy, and length of hospital stay.Results In-hospital mortality rate was 1.8% and 1-year mortality rate was 5.5%. At the final follow-up (mean 7 ± 6 years), the mortality rate was 45.4%. Seventy-four patients were lost to follow-up or refused to participate in the study. Forty-four patients responded to the survey and had a mean age of 73 years and mean follow-up of 7 ± 2 years. In the ODI questionnaire, disability grades were classified as minimal (23%), moderate (21%), severe (19%), complete (33%), and bed bound (4%). We found a significant correlation between inability to return to work and severe disability on ODI (p < 0.001), as well as a low score on any component of the SF-36 (p < 0.05).Conclusion Despite low in-hospital and 1-year mortality rates, patients with surgically treated pyogenic spondylodiskitis are prone to long-term limitation in all domains of quality of life, especially in physical health and work ability.
Keywords: spondylodiskitis; quality of life; Oswestry disability index; Short Form Work Ability Index; 36-Item Short Form Health Survey; Short Form Mcgill Pain Questionnaire